2009
DOI: 10.1016/j.mambio.2008.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of the wild boar population in Portugal: Evidence of a recent bottleneck

Abstract: The present study assesses the degree of genetic structure and the presence of recent genetic bottlenecks in the wild boar population in Portugal. One hundred and ten individuals were sampled after capture during organised legal drive hunts, conducted in 58 municipalities across the continental territory, during the game seasons of 2002/2003 and 2003/2004. Individuals were genetically typed at six microsatellite loci using multiplex PCR amplification. Significant deviations from Hardy-Weinberg equilibrium wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 42 publications
(36 reference statements)
7
59
1
5
Order By: Relevance
“…It is not known how long M. bovis has been present in wild boar populations in Portugal. One possible explanation of the pattern we observed is that five decades ago wild boar tuberculosis was restricted to historic refuges (Ferreira et al, 2008). From these refugia, wild boar populations expanded quickly throughout Portugal.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…It is not known how long M. bovis has been present in wild boar populations in Portugal. One possible explanation of the pattern we observed is that five decades ago wild boar tuberculosis was restricted to historic refuges (Ferreira et al, 2008). From these refugia, wild boar populations expanded quickly throughout Portugal.…”
Section: Discussionmentioning
confidence: 77%
“…Historic refuges of wild boar in Portugal correspond to their distribution during the first half of the 20th century ( Fig. 1) according to Ferreira et al (2008) and Lopes and Borges (2004).…”
Section: Risk Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…A remarkable genetic differentiation was revealed by Bayesian analysis also in other managed wild boar populations. In Portugal, Ferreira et al (2009) showed a latitudinal partition into three subpopulations, and interpreted it as possibly originating during the last century from isolated refuge nuclei. Similarly, three to four clusters stand out in a transboundary population in central Europe, although isolation by distance seemed to concur to this pattern (Frantz et al, 2009).…”
Section: Scandura Et Almentioning
confidence: 99%
“…This similarity would suggest that there might have been interchanges between North Africa and the European populations. While European wild boar have been studied widely with respect to genetic structure, hybridisation and phylogeography (Ferreira et al 2009;Koutsogiannouli et al 2010;Nikolov et al 2009;Scandura et al 2008;Vernesi et al 2003), there is as yet no study dealing with the North African part of the Communicated by C. Gortázar G. E. M. Hajji (*) : F. E. Zachos distribution range at the population level. In Tunisia, the wild boar is very common, widespread and the most important large game species.…”
Section: Introductionmentioning
confidence: 99%